HEAVY HYDROCARBONS IN SALSES (MUD VOLCANOES) OF THE TOREY BASIN, EASTERN TRANSBAIKAL - Krendelev F.P.; Fleshler V.I.; Cherednichenko V.P.; Shamsutdinov V.K. (My University, 1988)
Eastern Transbaikal within the Chita oblast is traditionally regarded as having no potential for oil, gas and salts because suitable sedimentary strata are absent here. However, it has long been known that in the Torey basin there are numerous examples of mud volcanism, called salses. Their formation here is considered to reflect the specificity of processes of freezing and thawing that occur in the transition zone from middle taiga forests to the Gobi Desert farther south within Mongolia. The Torey basin is tectonically most similar to areas with salt domes and petroliferous structures, as confirmed by the presence of large negative gravity anomalies under 'rings' of salt lakes. This paper reports on further evaluation from all available circumstantial evidence as far as the search for oil and gas shows or salt domes here is concerned, along with further direct geochemical criteria and, in particular, to locate hydrocarbon anomalies.